Deconstruction of Shari'ah Abdullahi Ahmed an-Na'im and the Idea of Substantive Islam - Kamal, Mustofa (Research and Development Institution, Darussalam Institute for Islamic Studies, 2020)
This article aims to explore the concept of deconstruction of Syari'ah Abdullahi Ahmed an-Na'im. In addition, this study also focuses on the contribution of the idea of Shari'ah deconstruction to the discussion of substantive Islam in Indonesia. Using critical analysis, this study finds that the deconstruction of sharia is an experiment of an-Na'im which is very basic considering that there is no methodology that can solve the paradox inherent in sharia which discriminates against women and non-Muslims. Therefore, important issues for the future of humanity need to be defined in Islam. The ideas offered by an-Na'im in stimulating the development of discussions about substantive Islam in Indonesia.